Case report: 18F-FDG PET/CT skeletal superscan-like in an adult patient with acute lymphoblastic leukemia - Hu, Yu; Dai, Wenli; Wang, Peng; Feng, Yawen; Feng, Hui; Li, Jun (Frontiers in Oncology, 2024)
We herein describe a rare case of adult acute lymphoblastic leukemia with 18 Florine-Fluorodeoxyglucose ( 18 F-FDG) Positron EmissionTomography/Computerized Tomography (PET/CT) skeletal superscan-like appearence. The degree of bone marrow uptake was so intense that it far exceeded the level of physiological cerebral uptake and radiourinary activity. The distribution was remarkably similar to superscan seen on skeletal scintigraphy. Skeletal superscan of 18 F-FDG PET/CT have been reported in hematological diseases, solid tumors with extensive bone metastasis and metabolic diseases. Thus, we reviewed the PET/CT images of cases reported, indicating that more homogeneous distribution, without primary tumor and specific mandibular and skull activity, may suggestive of hematological diseases.